Screening of microalgae for biosynthesis and optimization of Ag/AgCl nano hybrids having antibacterial effect. Issue 44 (15th August 2019) - Kashyap, Mrinal; Samadhiya, Kanchan; Ghosh, Atreyee; Anand, Vishal; Shirage, Parasharam M.; Bala, Kiran
Abstract : Here we report a facile and novel bio-synthesis technique, using algal extract to reduce silver metal ions into Ag/AgCl nanoparticles. Abstract : Here we report a facile and novel bio-synthesis technique, using algal extract to reduce silver metal ions into Ag/AgCl nanoparticles. Different concentrations of metallic precursors of silver nitrate (0.1 mM, 0.2 mM, 0.5 mM and 1 mM) were tested with alcoholic extract prepared from biomass of Chlorella sp. for nanoparticle biosynthesis which was screened out of four species namely Chlorella sp., Lyngbya putealis, Oocystis sp. and Scenedesmus vacuolatus . The biomolecules present in the alcoholic extract assisted in the synthesis of nanoparticles by reducing the metallic salt to metal ions and acting as capping agents in order to stabilize the particles. The synthesized particles were characterized for physico-chemical properties. DLS analysis of particles prepared from Chlorella sp. shows the particles with size of 90.6 nm. These biosynthesized nanoparticles show great potential applications in antibacterial activity.